Gruppenaufnahme - J.H. Darchinger
Geschäftsführer Friedrich-Ebert-Stiftung Horst Heidermann; Geschäftsführer Friedrich-Ebert-Stiftung a.D. Günter Grunwald; Leiter der Internationalen Abteilung der Friedrich-Ebert-Stiftung Siegfried Bangert;